The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1029/2022je007598
|View full text |Cite
|
Sign up to set email alerts
|

RIMFAX Ground Penetrating Radar Reveals Dielectric Permittivity and Rock Density of Shallow Martian Subsurface

Abstract: The Mars Rover Perseverance is the first NASA Rover with a ground penetrating radar (GPR) payload, the "Radar Imager for Mars' Subsurface Experiment" (RIMFAX) (Hamran et al., 2020). RIMFAX has continuously sounded the upper tens of meters of the Martian subsurface along the Rover traverse, taking the first in situ observations of the shallow Martian subsurface with its long microwave penetration. In this study, we analyze the first 8 km of data, starting at the Octavia E. Butler landing site, where Perseveranc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…That attenuation is similar over the Jezero Crater Floor, is in line with results from Hamran et al (2022) where maximum imaging depths are fairly constant. Casademont et al (2023) analyzed dielectric permittivity in the RIMFAX data and found only small differences between regions. Similar propagation velocities and similar attenuation estimates, could indicate that the shallow subsurface electrical properties are comparable over the whole investigated area.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…That attenuation is similar over the Jezero Crater Floor, is in line with results from Hamran et al (2022) where maximum imaging depths are fairly constant. Casademont et al (2023) analyzed dielectric permittivity in the RIMFAX data and found only small differences between regions. Similar propagation velocities and similar attenuation estimates, could indicate that the shallow subsurface electrical properties are comparable over the whole investigated area.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, all regions have mean values close to the combined estimate in (a), which for all soundings over the Crater Floor is Q* = 70.4 ± 7.7. At the RIMFAX 675 MHz center frequency, that equates to an attenuation of −2.6 ± 0.3 dB/m assuming a subsurface velocity of 0.1 m/ns (Casademont et al., 2023). Uncertainties are listed in terms of standard deviations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Radar Imager for Mars' Subsurface Experiment (RIMFAX) (150–1,200 MHz) aboard the Perseverance rover (Hamran et al., 2020) surveyed the Jezero crater (Hamran et al., 2022). The average permittivity detected by the RIMFAX on Perseverance in the Jezero Crater is 9.0 ± 2.8, with a mean depth of 1.9 ± 1.1 m (Casademont et al., 2022). The observed slopes, thicknesses, and internal morphology of the inclined stratigraphic sections by RIMFAX can be interpreted either as a magmatic layering formed in a differentiated igneous body or as a sedimentary layering commonly formed in aqueous environments on Earth (Hamran et al., 2022).…”
Section: Discussionmentioning
confidence: 99%